Getting to Know PPnBM : Salex Tax and Luxury goods and analyzing the impact On Consumer Purchasing Power and Value added Tax and sales Tax on luxury Good in the Motor Vehicle sector - Alya Safana; Siti Nur Hidayah; Pasya Namira; Syafira Cahya Ramadhani; Galih Supraja (CV. AFDIFAL MAJU BERKAH, 2025)
This research is motivated by various issues related to consumer purchasing power for motor vehicles, particularly in the context of Value Added Tax (VAT) and Luxury Goods Tax (LGT).The aim is to explore the impact of these two types of taxes on consumer purchasing power formotor vehicles. A qualitative descriptive approach was utilized, involving literature studies thatgathered references from articles and online sources. In addition, it involves data collectionand analysis from various literature relevant to the research topic used to study tax concept,PPnBM, buyer's purchasing power and vehicle characteristics, collecting existing information and theory, identifying relationships between variables, and analyzing the impact of PPnBM on consumer purchasing power based on secondary data from a variety of different sources.The findings indicate that both VAT and LGT significantly influence consumer purchasingpower for motor vehicles simultaneously; however, VAT alone does not show significant impact, while LGT proves to be significantly influential on consumer buying capability.